Different impulse control disorder evolution patterns and white matter microstructural damage in the progression of Parkinson’s disease - Hu, Ling; Lin, Changfu; Lin, Fabin; Wang, Lingling; Li, Zhenzhen; Cai, Zhijun; Liu, Xianghong; Ye, Qinyong; Wu, Yiwen; Cai, Guoen (Frontiers in Aging Neuroscience, 2023)
Background: The course of impulse control disorders ((ICD) )variates in the early stage of Parkinson's disease (PD). Aim: We aimed to delineate the association between the evolution pattern of ICD and the progression of Parkinson's diseasePD (PD). Methods: 321 de novo PD patients from the Parkinson's Progression Markers Initiative database were included. Patients were followed up for a mean of 6.8 years and were classified into different groups according to the evolution patterns of ICD. Disease progression was compared among groups using survival analysis, where the endpoint was defined as progression to Hoehn-Yahr stage 3 or higher for motor progression and progression to mild cognitive impairment for cognitive decline. In the 4th year of follow-up, four types of ICD evolution patterns were identified: (1) non-ICD-stable (68.2%): a patient who is consistently free of ICD; (2) late-ICD (14.6%): ICD developed during follow-up of patients; (3) ICD-stable (11.5%): patients showed persistent ICD, and (4) ICD-reversion (5.6%): baseline ICD disappeared during follow-up of patients with ICD. Results: ICD-reversion type showing symptoms of the daily life of non-motor symptoms (NMS) (Movement Disorder Society-Unified Parkinson Disease Rating Scale (MDS-UPDRS) part Ⅰ), daily life motor symptoms (MDS-UPDRS part Ⅱ), rapid eye movement sleep behavior disorder (RBD), and anxiety symptoms have a greater impact. PD patients with different ICD evolution patterns had different changes in white matter microstructure at the onset of the disease. Those relevant brain regions are involved in ICD and non-motor functions. Conclusion: Four early ICD evolution are identified in de novo PD, with different prognoses and brain white matter microstructural damage patterns, and it may predict motor progression and cognitive decline in PD patients. Based on these results, ICD evolution patterns in PD may have prognostic value.